PEARLMILLET AND MUNGBEAN INTERCROPPING AS INFLUENCED BY VARIOUS ROW RATIOS UNDER CUSTARD APPLE ORCHARD OF VINDHYAN REGION - Y. K. GHILOTIA; R. N. MEENA; LAKHAPATI SINGH (The Bioscan, 2014)
A field experiment was conducted during 2010-11 to study the “Pearlmillet and Mungbean intercropping as influenced by various row ratios under custard apple orchard of vindhyan region”. The highest grain wt. (14.25g)/ear head, test weight (8.56g), ear diameter (3.13cm), ear length (14.25cm) and ear wt. (31.15g) of pearlmillet and pod length (5.47cm), number of pod/plant (12.57) and number of grain/pod (8.03), test weight (44.33g) of mungbean were recorded under pearlmillet + mungbean (2:2) in intercropping row ratio. Whereas grain yield (1568.40 kg/ha), straw yield (5192.23 kg/ha), biological yield (6760.63 kg/ha) and mean pearlmillet grain equivalent yield (4817.03 kg/ha) of pearlmillet and grain yield (696.14 kg/ha), straw yield (1853.29 kg/ha), biological yield (2549.43 kg/ha) of mungbean were highest under pearlmillet sole and mungbean sole as compared to intercropping row ratio. Similarly, nitrogen in grain and phosphorus in grain, straw and total nitrogen and phosphorus uptake were maximum in pearlmillet sole and mungbean sole as compared to other treatments. The maximum nitrogen uptake in straw (23.44 kg/ha), protein content in pearlmillet (11.94%) and mungbean grain (23.82%), land equivalent ratio (1.04) and relative crowding coefficient of pearlmillet (1.74) and mungbean (2303.23) were observed in pearlmillet + mungbean (2:2) in intercropping row ratio. The highest aggressivity (7.58) was recorded in treatment pearlmillet + mungbean (2:1) in intercropping row ratio as compared to other treatments.